2011
DOI: 10.1177/0194599810397793
|View full text |Cite
|
Sign up to set email alerts
|

Personality Types of Otolaryngology Resident Applicants as Described by the Myers‐Briggs Type Indicator

Abstract: This study examines the personality types of medical students applying to an otolaryngology residency. The results support a highly structured, data-driven teaching preference among applicants. These results may allow for a better understanding of the personalities of medical students who are interested in otolaryngology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…It was found that otolaryngology applicants were likely to have an Extravert-ST-Judging personality profile. These investigators also reported that Thinking (T) and Judging (J) types were more common than Feeling (F) and Perceiving (P) types among the otolaryngology residency applicants (Zardouz et al 2011).…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 92%
See 2 more Smart Citations
“…It was found that otolaryngology applicants were likely to have an Extravert-ST-Judging personality profile. These investigators also reported that Thinking (T) and Judging (J) types were more common than Feeling (F) and Perceiving (P) types among the otolaryngology residency applicants (Zardouz et al 2011).…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 92%
“…However, those choosing ophthalmology were more people-oriented and those choosing otolaryngology were more technology-oriented. The proportion of Extravert-ST-Perceiving type was significantly higher in otolaryngology residency applicants (8%) than the general population (3%) (Zardouz et al 2011). In different studies, personality types of physiatrists (Sliwa & Shade-Zeldow 1994), pediatric residents (Lacorte & Risucci 1993) and emergency department staff have been compared (Boyd & Brown 2005), and no pronounced differences in their personality types have emerged.…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 99%
See 1 more Smart Citation
“…MBTI is one of the most popular psychological instruments to measure an individual's preference (Zardouz, 2011), attitudes and perceptions (Buboltz, 2000). Contemporary business practice still benefi ts from MBTI with approximately three million individuals fi lling the questionnaires every year.…”
Section: The Myers-briggs Type Theorymentioning
confidence: 99%
“…Hence, the identification of them based on the type of personality might help in their association with coworkers, students, 555 JCDP and patients. [9][10][11] Identification of the individual preferences toward different specialties in dentistry can be helpful in identifying individual choices. No studies were performed to classify the personality types of dentists working in various disciplines in dentistry.…”
Section: Introductionmentioning
confidence: 99%